Seasonality analysis of Lithuanian stock market - Lukas Macijauskas (Business: Theory and Practice, 2010)
The main purpose of this article is to test if there are any seasonal tendencies in Lithuanian stock market and if so, do they match seasonal anomalies found in other countries. To achieve this ambition, tests were done by dividing returns of OMXV index into three groups: month of the year, week of the month and day of the week. Analysis was made using 10 years of historical data which covers main stages of Lithuanian stock market cycle. Results show that seasonal anomalies do exist in Lithuanian stock market and that their characteristics are similar to those found by researches in other stock markets.